Action Research: Improving the Professional Competence of Prospective Islamic Counselors with Content Mastery Services - Agus Sukirno; Yogi Damai Syaputra; Nina Fitriyani; Monalisa Monalisa; Trisna Taufik Darmawansyah (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study aims to improve prospective counselors' professional competence by implementing content mastery services based on action research. This research is important due to the complexity of social problems and clients' diverse cultural and religious backgrounds. The research was conducted in two cycles, with planning, action, observation, and reflection stages, encompassing theoretical training, counseling simulations, case discussions, and structured practice. The study subjects were students of the Islamic Guidance Counseling Study Program. Data were collected through observation, interviews, documentation, and reflection. The improvement focus was directed at six competency indicators: assessment of client needs, mastery of theory and practice, program design and implementation, service evaluation, and integration of Islamic values. The study results showed a significant increase in all indicators after implementing Cycle II. Students showed development in assessment skills, more systematic service implementation, and the ability to contextualize Islamic values in counseling practice. Content mastery services designed in a reflective, applicative, and value-based manner have proven effective in improving the professional competence of prospective Islamic counselors. These findings can be applied in counselor training in various Islamic educational institutions. Keywords: action research, content mastery services, professional competence